EFEK SERETAN KERANGKA INERSIAL DI DALAM MEDAN BINTANG NEUTRON YANG BEROTASI DAN STASIONER - Tika Restianingsih; Muhammad Farchani Rosyid (JOURNAL ONLINE OF PHYSICS, 2020)
The inertial frame dragging effect of rotating neutron star has been studied. Inertial frame dragging effect, also well known as Lense Thirring effect, has been predicted using general theory of relativity in 1918. When the neutron star rotates very quickly, the space time around it will be dragged to the direction of the rotation. The Lense Thirring effect is small enough for small objects so it will be clearly seen for massive objects like compact stars, especially neutron star. Later, we derive the equation of frame dragging rate () inside the rotating neutron star, which is axisymmetrik and stationary. Frame dragging rate is decreasing from the center to the surface of stars. It is also noted that is proportional to the angular velocity of star.